A plea for 'genealogical thinking' in comparative biology – a rebuttal to the reply of Szucsich, Wirkner, and Pass to my article 'Deconstructing Morphology'. (23rd November 2011) - Scholtz, Gerhard
Abstract Scholtz G. in press. A plea for 'genealogical thinking' in comparative biology – a rebuttal to the reply of Szucsich, Wirkner, and Pass to my article 'Deconstructing Morphology'. —Acta Zoologica (Stockholm) 00: 1–4. Szucsich et al. (in press) claim that – in contrast to my statement – morphological thinking has to be 'cladistic.' Based on this premise, they stress the difference between the relationships among states of characters versus those among structures assigned to the same character state as implemented in numerical cladistic reasoning. SEA claim that my approach to the homology concept only deals with the problem of the integration of various character states into the same character, whereas the necessary relationships among structures assigned to the same state are not covered. Based on this distinction, SEA also criticise the application of similarity in my definition of homology. Furthermore, they address the issue of evolutionarily independent units.